Delineation of the complex microbial nitrogen-transformation network in an anammox-driven full-scale wastewater treatment plant. (15th May 2023) - Hu, Pengfei; Qian, Youfen; Liu, Jinye; Gao, Lin; Li, Yuxin; Xu, Yanbin; Wu, Jiapeng; Hong, Yiguo; Ford, Tim; Radian, Adi; Yang, Yuchun; Gu, Ji-Dong
Highlights: Rational cascading of reactors achieves high n removal (99.6%) in full-scale WWTP. Overall nitrogen transformation network was reconstructed for the de-ammonification processes. Anammox bacteria were enriched naturally in biofilm because of niche and metabolic versatility. 15 N isotope labeling confirms 83% contribution of anammox to n removal. Two distinct anammox bacteria were identified. Abstract: Microbial-driven nitrogen removal is a crucial step in modern full-scale wastewater treatment plants (WWTPs), and the complexity of nitrogen transformation is integral to the various wastewater treatment processes. A full understanding of the overall nitrogen cycling networks in WWTPs is therefore a prerequisite for the further enhancement and optimization of wastewater treatment processes. In this study, metagenomics and metatranscriptomics were used to elucidate the microbial nitrogen removal processes in an ammonium-enriched full-scale WWTP, which was configured as an anaerobic-anoxic-anaerobic-oxic system for efficient nitrogen removal (99.63%) on a duck breeding farm. A typical simultaneous nitrification-anammox-denitrification (SNAD) process was established in each tank of this WWTP. Ammonia was oxidized by ammonia-oxidizing bacteria (AOB), archaea (AOA), and nitrite-oxidizing bacteria (NOB), and the produced nitrite and nitrate were further reduced to dinitrogen gas (N2 ) by anammox and denitrifying bacteria. Visible red anammox biofilms were formed successfully on the sponge carriers submerged in the anoxic tank, and the nitrogen removal rate by anammox reaction was 4.85 times higher than that by denitrification based on 15 N isotope labeling and analysis. This supports the significant accumulation of anammox bacteria on the carriers responsible for efficient nitrogen removal. Two distinct anammox bacteria, named " Ca . Brocadia sp. PF01" and " Ca . Jettenia sp. PF02", were identified from the biofilm in this investigation. By recovering their genomic features and their metabolic capabilities, our results indicate that the highly active core anammox process found in PF01, suggests extending its niche within the plant. With the possible contribution of the dissimilatory nitrate reduction to ammonium (DNRA) reaction, enriching PF02 within the biofilm may also be warranted. Collectively, this study highlights the effective design strategies of a full-scale WWTP with enrichment of anammox bacteria on the carrier materials for nitrogen removal and therefore the biochemical reaction mechanisms of the contributing members. Graphical abstract: Image, graphical abstract